(untitled) (Gestión y Gerencia, 2022)
The Venezuelan meat industry has traveled a path little studied within the approach of technological management. This study explores the experience of the Empresa Productos Alimex CA, which after 63 years of production has managed to position itself as the third company in the country. The objective is to analyze this management process in its learning and assimilation in the production process, as well as technology transfer and its link with the academy. The methodology followed is qualitative with field design and consists of gathering information through interviews with partners, founders, directors, engineers, technicians and workers, through the use of open and specific questions. Additionally, a bibliographic review of primary and secondary sources was carried out. Among the conclusions, they highlight that the process of learning, assimilation and transfer of knowledge was initially informal. Capacitation is formed through courses, training practices. and close links with the academy, which have provided a timely response. Learning based on "learning by doing" has been strengthened with formal and academic training. This contribution aims to improve the understanding of technological management in Venezuelan companies and show that this capacity exists in the country.